VD_FINDINFO AP / 2011 / 70 vom 8. April 2010 - VD Tribunal cantonal (2010)
BAIL À LOYER, RÉSILIATION ABUSIVE, CONGÉ DE REPRÉSAILLES, USAGE PERSONNEL, ACTIONNAIRE UNIQUE, SOCIÉTÉ ANONYME | 2 al. 1 CC, 2 al. 2 CC, 271 al. 1 CO, 271a al. 1 let. a CO, 444 al. 1 ch. 3 CPC, 451 ch. 2 CPC, 452 al. 1 CPC, 452 al. 2 CPC, 456a CPC, 13 LTB, 405 al. 1 CPC (CH)